Pregnant women with altered pulsatility index in Doppler echography - Julio Ernesto Rodríguez Serret; Acelia Salmon Cruzata; Sahily Quintero Salcedo; Leslie Navi Leiva Pablo (Centro Provincial de Información de Ciencias Médicas, 2020)
Introduction: The Doppler echography of the uterine arteries is a technique suggested to predict the risk of pre-eclampsia, the intrauterine growth retardation and other adverse perinatal disorders. Objectives: To determine the frequency of pregnant women with disorder in the uterine arteries during the first trimester and to identify the pre-eclampsia/eclampsia presence, as well as their main clinical characteristics. Methods: A descriptive and longitudinal study of 168 pregnant women in the first trimester of pregnancy, belonging to the Tercer Frente municipality in Santiago de Cuba was carried out, they were evaluated by investigation of Genetics in Cruce de los Baños Teaching Polyclinic from April to November, 2018. To determine the pulsatility index of the uterine arteries, a Doppler echography was carried out. Results: In the case material 16 patients presented this parameter altered and just 3 pregnant women presented pre-eclampsia, for 18.7 %; the average age of these last ones was of 29 years and 2 were nonparous (66.6 %). Regarding the pulsatility index, the average was of 2.5. Conclusions: There was a close follow up of the patients with pathological results, until the childbirth, and the importance of studying the pulsatility index of the uterine arteries in the first trimester of the pregnancy, mainly in the nonparous, was emphasized.